4D-Fast Data-Independent Acquisition Quantitative Proteomic Identification and Functional Analysis of Differentially Expressed Proteins between Selenium-Enriched and Non-Selenium-Enriched Eggs - YUAN Lin, ZHAO Wenzhu, WU Chunjian, YU Yiding, YU Zhipeng (Shipin Kexue)
This study applied 4D-fast data-independent acquisition (DIA) quantitative proteomics for the identification and functional analysis of the differentially expressed proteins between selenium-enriched and non-selenium-enriched eggs. A quantitative proteomic analysis of selenium-enriched eggs was performed using liquid chromatography-tandem mass spectrometry (LC-MS/MS) combined with bioinformatics. The relative quantification of proteins between groups was performed to explore the differential expression patterns of proteins, and protein functions and metabolic pathways were analyzed using Gene Ontology (GO) annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses. Proteomic analysis identified a total of 257 proteins, of which 251 were quantified. Forty-eight differentially expressed proteins were identified in egg white, with 28 being down-regulated and 20 being up-regulated. A total of 82 differentially expressed proteins were identified in egg yolk, with 58 being down-regulated and 24 being up-regulated. The expression levels of serine peptidase inhibitor, immunoglobulin-like domain-containing proteins, ovotransferrin, and mucin-6 were significantly higher in naturally selenium-enriched eggs than in non-selenium-enriched eggs, based on a comparative analysis of protein expression profiles. Go annotation and KEGG pathway enrichment analyses revealed that proteins associated with immune regulation, antibacterial activity, and antioxidant functions were significantly higher expressed in naturally selenium-enriched eggs compared with non-selenium-enriched eggs. These findings provide a scientific basis for understanding the difference in nutritional value between selenium-enriched eggs and non-selenium-enriched eggs, as well as the underlying molecular mechanisms.